2017
DOI: 10.12783/issn.1544-8053/14/1/29
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of S-metolachlor and its Effects on Soil Enzymes and Microbial Communities in Vegetable Field Soil

Abstract: S-metolachlor is a promising alternative to metolachlor. However, the extensive use of S-metolachlor as herbicide in vegetable fields in China has caused concerns about its environmental fate. Here we investigated the effects of temperature, relative humidity (RH) and PH on the degradation rate of S-metolachlor in vegetable soil. The degradation rates of S-metolachlor increased with increasing temperatures and RH and either acidic or basic PH facilitates S-metolachlor degradation. The degradation of S-metolach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Although the physiochemical properties of the organic soil is different from soils in previous S-metolachlor field dissipations studies, the half-life of 50 to 126 d is within the range of 13 to 142 d reported in previous field studies (Frank et al 1991;Huang et al 2017;Martínez et al 1997;Mueller et al 1999; Figure 2. Dissipation of S-metolachlor in the top 7.5 cm of organic soil in sugarcane fields in 2013 to 2014 and 2014 to 2015 growing seasons at the Everglades Research and Education Center in Belle Glade, FL.…”
Section: Organic Soilssupporting
confidence: 55%
See 2 more Smart Citations
“…Although the physiochemical properties of the organic soil is different from soils in previous S-metolachlor field dissipations studies, the half-life of 50 to 126 d is within the range of 13 to 142 d reported in previous field studies (Frank et al 1991;Huang et al 2017;Martínez et al 1997;Mueller et al 1999; Figure 2. Dissipation of S-metolachlor in the top 7.5 cm of organic soil in sugarcane fields in 2013 to 2014 and 2014 to 2015 growing seasons at the Everglades Research and Education Center in Belle Glade, FL.…”
Section: Organic Soilssupporting
confidence: 55%
“…This shows that persistence of S-metolachlor in the second season was 2.3-fold that of the first season. S-metolachlor half-lives of 13 to 142 d under field conditions depending on soil type and prevailing environmental conditions have been previously reported (Frank et al 1991;Huang et al 2017;Martínez et al 1997;Mueller et al 1999;Shaner and Henry 2007;Shaner et al 2006;Westra et al 2014;Wu et al 2015). An exponential decay model, with the exception of Shaner et al (2006) and Westra et al (2014), described dissipation dynamics of S-metolachlor in these previous studies.…”
Section: Organic Soilsmentioning
confidence: 79%
See 1 more Smart Citation